TOXICITY OF THE BIOPESTICIDES AGAVE AMERICANA, FURCRAEA ANDINA (ASPARAGACEAE) AND SAPINDUS SAPONARIA (SAPINDACEAE) ON INVADER SNAIL MELANOIDES TUBERCULATA (THIARIDAE) - Iannacone, José (2013)
One of the most studied plant families in the search for new therapeutic agents is the Asparagaceae, comprising 2480 species, Agave americana L. with the common name maguey and Furcraea andina Trel., named fique plant belong in this family. Sapindus saponaria L. (Sapindaceae) known as western soapberry is a widely distributed tree, whose fruit was observed to have larvicidal effects on ticks, antimicrobial activity, spermicide, fungicide and molluscicide. Melanoides tuberculata (Muller 1774) (Gastropoda: Thiaridae) is a snail with cosmopolitan distribution especially in tropical areas with high ecological importance. The invasive impact on the diversity of threatened native snails, or at least decrease the native shellfish populations, due to its high biotic potential and high reproductive rate. Thus, the objective of this study was to evaluate the acute toxicity of leaves of A. americana, F. andina and fruit of S. saponaria on M. tuberculata. The endpoint was mortality of the snail M. tuberculata to 24 hr of exposure, with recovery in clean water to 24 hr. The values o?f LC (median lethal concentration), NOEC (no 50 observable effect concentration) and LOEC (lowest concentration of observable effects) had the following sequence in order of decreasing toxicity: A. americana> F. andina> S. saponaria. The aqueous extract of A. americana molluscicides showed the best effects on M. tuberculata compared to the other two plants used.